2019
DOI: 10.1111/cns.13121
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ENST00000413528 sponges microRNA‐593‐5p to modulate human glioma growth via polo‐like kinase 1

Abstract: Summary Aims In this study, we examined the expression of lncRNA ENST00000413528 in glioma and determined its role in glioma development. Methods LncRNA ENST00000413528 was detected in glioma tissues by lncRNA microarray. Then, we performed real‐time PCR, CCK‐8, colony formation assay, flow cytometry, caspase‐3/7 assay and animal experiment to detect the function of ENST00000413528 in glioma after ENST00000413528 knockdown. Subsequent bioinformatics analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Previous studies show that the Polo-like kinase 1(PLK1) is highly expressed in LC, which predicts the poor survival in metastatic LC patients [56,57]. In addition, the PLK1 pathway plays a certain role in the progression of HCC [58], glioma [59], and lung adenocarcinoma [60]. e current research systemically examines the expression of CDCA genes and its prognostic significance in LC, which sheds more light on the complexity and heterogeneity of LC biological properties at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies show that the Polo-like kinase 1(PLK1) is highly expressed in LC, which predicts the poor survival in metastatic LC patients [56,57]. In addition, the PLK1 pathway plays a certain role in the progression of HCC [58], glioma [59], and lung adenocarcinoma [60]. e current research systemically examines the expression of CDCA genes and its prognostic significance in LC, which sheds more light on the complexity and heterogeneity of LC biological properties at the molecular level.…”
Section: Discussionmentioning
confidence: 99%
“…GSEA analysis of all genes in the three datasets revealed specific pathway enrichments. The COVID-19 dataset showed enrichment in the PLK1 pathway, associated with stem cell cancer ( 50 ), glioma ( 51 ), and lung adenocarcinoma ( 52 ). The influenza dataset exhibited enrichment in the oxidative stress response signaling pathway, a potential therapeutic target for gastric cancer ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 has been verified to be involved in various cancers, such as hepatocellular carcinoma 40 , breast cancer 41 , prostate cancer 42 , acute myeloid leukemia 43 . Additionally, PLK1 has been reported to be upregulated in glioma and can markedly promote cell proliferation and migration 44 - 46 . Moreover, we demonstrated that circ-ZNF609 could promote the expression of PLK1 via sponge miR-1224-3p.…”
Section: Discussionmentioning
confidence: 99%